2021
DOI: 10.1094/pdis-08-20-1777-re
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Rice Expressing Isoflavone Synthase Gene from Soybean Shows Resistance Against Blast Fungus (Magnaporthe oryzae)

Abstract: The isoflavones are a group of plant secondary metabolites primarily synthesized in legumes and are known for their role in improving human health and plant disease resistance. The isoflavones, especially genistein, act as precursors for the production of phytoalexins, which may induce broad-spectrum disease resistance in plants. In the present study, we screened transgenic rice lines expressing the isoflavone synthase (GmIFS1) gene from soybean for rice blast (Magnaporthe oryzae) resistance. Two homozygous tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…61 The increase in genistein concentration led to an increase in the concentration of downstream isoflavones, such as genistin and Biochanin A. Transgenic rice, expressing isoflavone synthase gene from soybean, showed resistance to Magnaporthe oryzae, and this effect was attributed to the synthesis of genistein in rice. 62 Cheng et al reported that isoflavone synthase expression was correlated with the increase in disease resistance to soybean mosaic virus. 63 Silencing of genes for daidzein biosynthesis increased the concentrations of genistein and its derivatives but reduced the resistance to P. sojae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…61 The increase in genistein concentration led to an increase in the concentration of downstream isoflavones, such as genistin and Biochanin A. Transgenic rice, expressing isoflavone synthase gene from soybean, showed resistance to Magnaporthe oryzae, and this effect was attributed to the synthesis of genistein in rice. 62 Cheng et al reported that isoflavone synthase expression was correlated with the increase in disease resistance to soybean mosaic virus. 63 Silencing of genes for daidzein biosynthesis increased the concentrations of genistein and its derivatives but reduced the resistance to P. sojae.…”
Section: Discussionmentioning
confidence: 99%
“…Transgenic soybean plants with enhanced isoflavone biosynthesis showed a 4.36‐fold increase in genistein concentration and enhanced resistance to mosaic virus 61 . The increase in genistein concentration led to an increase in the concentration of downstream isoflavones, such as genistin and Biochanin A. Transgenic rice, expressing isoflavone synthase gene from soybean, showed resistance to Magnaporthe oryzae , and this effect was attributed to the synthesis of genistein in rice 62 . Cheng et al .…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been shown to increase the resistance of alfalfa ( Medicago sativa ) to Acyrthosiphon pisum [ 47 ], and of rice ( O . sativa ) to Magnaporthe oryzae [ 48 ]. Genistein can also improve the response of plants to adverse environmental conditions.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to genes from Arabidopsis , transgenic rice plants expressing resistant Lr34 allele from wheat showed increased resistance against multiple isolates of the hemibiotrophic pathogen M. oryzae by delaying invasive hyphal growth [ 133 ]. In another example, transgenic rice lines expressing the isoflavone synthase (GmIFS1) gene from soybean contributed to the synthesis of isoflavone (genistein) to promote M. oryzae resistance, indicating that the synthesis of heterologous secondary metabolites, such as isoflavone, is a good way to develop blast resistance in rice [ 134 ]. As such, we believe that engineering resistant rice through ectopic transcription of defense genes cloud be a broadly applicable new strategy, which may lead to reduced use of pesticides and lightening the selection pressure of resistance pathogens.…”
Section: Strategies For Broad-spectrum Disease Resistance Rice Breedingmentioning
confidence: 99%